The tragedy of Romeo and Juliet - Shakespeare, William, 1564-1616.; Mowat, Barbara A.; Werstine, Paul.; Folger Shakespeare Library (New York : Washington Square Press, 1992)
Presents the text of Shakespeare's drama about Romeo and Juliet, two young people whose love is doomed by their warring families, and includes explanatory notes, plot summaries, a key to famous lines and phrases, a modern perspective on the play, and other reference tools.
Cover title: Romeo and Juliet.
Includes bibliographical references (p. 267-278).
Young Adult
Keywords: Juliet (Fictitious character) -- Drama; Romeo (Fictitious character) -- Drama; Vendetta -- Drama; Youth -- Drama; English drama; Juliet (Fictional character) -- Drama; Romeo (Fictional character) -- Drama; Tragedies; Vendetta -- Drama; Youth -- Drama; Verona (Italy) -- Drama; Verona (Italy) -- Drama